Delivery Hospital Characteristics and Postpartum Maternal Mortality: A National Case-Control Study in France. Issue 2 (June 2020) - Saucedo, M.; Bouvier-Colle, M.H.; Blondel, B.; Bonnet, M.P.; Deneux-Tharaux, C.
Abstract : ( Anesth Analg . 2020;130:52–62) While obstetric care providers are always focused on ensuring the best outcomes for their patients, not much empirical evidence is available to illustrate how a hospital's organizational structure can affect maternal and neonatal outcomes. Research has shown that premature infants who are transferred to specialty centers experience better health outcomes, but there is variability in how facilities classify maternal risk factors that would indicate a need for preterm delivery. This inconsistency in procedure presents a number of maternal health risks, and so Saucedo and colleagues conducted their study to determine how a hospital's organizational characteristics affect the risk of postpartum maternal death.